The Pros and Cons of Dental Laser Therapy in Conservative Dentistry and Endodontics—A Systematic Review - Priyanka Sarangi; Shradha Suman; Sukanta Kumar Satapathy; Rinki Meher; Abhisek Das; Divya M Pradeep (Journal of Pharmacy and Bioallied Sciences)
The objective of this systematic review was to investigate the clinical evidence on the utilization of lasers in endodontics and evaluate the advantages and disadvantages associated with its use. The search engines, such as PubMed, Cochrane, and Scopus, were utilized to locate human clinical trials pertaining to the application of lasers in endodontic therapy. By utilizing keywords, additional filters, and inclusion and exclusion criteria, the initial pool of 387 articles was narrowed down to 12. Laser reduces endodontic postoperative discomfort and improves patient satisfaction, according to research.